Empire's Violent End Comparing Dutch, British, and French Wars of Decolonization, 1945-1962 - Brocades Zaalberg, Thijs; Luttikhuis, Bart (Cornell University Press, 2022)
In Empire's Violent End, Thijs Brocades Zaalberg and Bart Luttikhuis, along with expert contributors, present comparative research focused specifically on excessive violence in Indonesia, Algeria, Vietnam, Malaysia, Kenya, and other areas during the wars of decolonization. In the last two decades, there have been heated public and scholarly debates in France, the United Kingdom, and the Netherlands on the violent end of empire. Nevertheless, the broader comparative investigations into colonial counterinsurgency tend to leave atrocities such as torture, execution, and rape in the margins. The editors describe how such comparisons mostly focus on the differences by engaging in "guilt ranking." Moreover, the dramas that have unfolded in Algeria and Kenya tend to overshadow similar violent events in Indonesia, the very first nation to declare independence directly after World War II. Empire's Violent End is the first book to place the Dutch-Indonesian case at the heart of a comparison with focused, thematic analysis on a diverse range of topics to demonstrate that despite variation in scale, combat intensity, and international dynamics, there were more similarities than differences in the ways colonial powers used extreme forms of violence. By delving into the causes and nature of the abuse, Brocades Zaalberg and Luttikhuis conclude that all cases involved some form of institutionalized impunity, which enabled the type of situation in which the forces in the service of the colonial rulers were able to use extreme violence.